IMPLEMENTASI KONTROL SUHU AC (AIR CONDITIONER) PADA RUANGAN MEETING SECARA OTOMATIS MENGGUNAKAN METODE FUZZY LOGIC BERBASIS IOT - Firly Akbar, Ahmad; Abdurrahman; Rasyad, Sabilal (JURNAL TELISKA, 2023)
Meeting rooms are important environments in terms of productivity and user comfort. The right temperature in a meeting room plays an important role in improving the concentration, performance, and comfort of meeting participants who are discussing. However, manually adjusting the temperature of the AC in the room is often a complicated and time-consuming task. Therefore, there is a need for an automatic device that can control the AC temperature effectively and efficiently. Key words : AC temperature controller, Internet of Things, Fuzzy Logic